Human Plasma In‐Cell Western Assays—An In vitro Predictor for In vivo Pharmacology in Oncology Drug Discovery. Issue 2 (15th February 2021) - Zhang, Yang W.; Gallagher, Kirsten; Angelis, Dimitrios; Rominger, Dave; Scherle, Peggy; Vaddi, Kris
Abstract: Evaluation of in vivo potencies plays an important role in drug discovery. Traditionally, the cellular activity and percent of plasma protein binding of a test agent are evaluated separately, with the plasma protein binding−adjusted cellular potency computation used to estimate in vivo potency. This process is costly, takes weeks to complete, and is increasingly unreliable for compounds that bind extensively to plasma proteins. Described in this article is a simple, high‐throughput human plasma in‐cell Western (ICW) assay that directly incorporates plasma protein binding into a cellular pharmacodynamic assay to provide a rapid and accurate estimate of in vivo potencies. The assay is versatile and can be readily employed for various targets that require short treatment periods for displaying maximal biological responses. © 2021 Wiley Periodicals LLC. Basic Protocol : Concentration‐dependent human plasma ICW assay to determine test compound IC50 against the target of interest